Analisis Rasio dan Penilaian Prestasi pada Perusahaan Tri Banyan Tirta Tbk Periode 2020-2022 - Dewi, Putri Purnama; Sianturi, Ria Crisna (CV. Kalimasada Group, 2024)
A company performance evaluation report is a document used to assess and analyze the operational, financial, and strategic performance of a company over a certain period. This report typically covers various aspects such as sales, profits, productivity, efficiency, and the achievement of company goals. This research aims to determine the financial performance of the company evaluated through financial ratio analysis, which includes liquidity ratios, solvency ratios, profitability ratios, and activity ratios of PT. Tri Banyan Tirta Tbk from 2020 to 2022. The data collection technique is conducted through literature study, which involves searching for information sources related to ratio analysis and literature review on PT Tri Banyan Tirta Tbk. The results of this analysis based on liquidity ratios, viewed from the current ratio and quick ratio, indicate that the company's financial performance is considered poor. Based on solvency ratios, viewed from the debt to assets ratio and debt to equity ratio, the company's financial performance is considered poor. Based on profitability ratios, viewed from the net profit margin, Return on Assets, and Return on Equity, the company's financial performance is considered very poor. The results of this study indicate that the company's financial performance declined during the research period. Therefore, efforts are needed to improve the company's financial performance in implementing business strategies